Correlates of unprotected sexual intercourse among women who inject drugs or who have sexual partners who inject drugs in St Petersburg, Russia. Issue 3 (2nd February 2013) - Abdala, Nadia; Hansen, Nathan B; Toussova, Olga V; Krasnoselskikh, Tatiana V; Verevochkin, Sergei; Kozlov, Andrei P; Heimer, Robert
Abstract : Objectives: To assess risk for unintended pregnancy, this study describes the correlates of unprotected sexual intercourse (UPSI) among women who inject illicit drugs or who have sexual partners who inject drugs in St Petersburg, Russia. Methods: Data from a cross-sectional survey and biological test results collected between 2005 and 2008 from 202 Russian women (143 drug injectors and 59 non-drug injectors) were analysed. Multivariate regression was used to investigate the correlates of UPSI occurring at the women's last sexual act. Independent variables included socio-demographics, age at sexual debut, first sexual encounter perceived as involuntary, number of pregnancies and number of children for which the participant is the primary caretaker, heavy sporadic drinking (i.e. consuming more than five drinks in 2 hours at least twice a month), at-risk drinking per the Alcohol Use Disorder Identification Test (AUDIT-C) score, and sexually transmitted infections (HIV-1, syphilis serology, Chlamydia trachomatis and Neisseria gonorrheae ). Results: Sixty-seven percent of women reported UPSI at last intercourse. UPSI was independently associated with heavy sporadic drinking [odds ratio (OR) 2.8, 95% CI 1.2–6.6] and having been pregnant (OR 2.25, 95% CI 1.1–4.6). Conclusions: Despite the high risk for HIV acquisition or transmission and unintended pregnancy, condom use among the study population is low. Programmes to investigate and improve contraceptive use, including condom use, among this vulnerable group of women are needed. Such programmes may require identifying and targeting female reproductive health concerns and problem drinking, particularly heavy sporadic drinking, rather than conventional measures of alcohol misuse.